2005
DOI: 10.1021/ef049718g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Steam Reforming of Bio-Oil Using Coprecipitated Ni−Al Catalysts. Acetic Acid as a Model Compound

Abstract: Catalytic steam reforming of bio-oil is a promising process for hydrogen production from biomass. Bio-oil is a complex mixture of a large number of compounds (acids, aldehydes, alcohols, and ketones, among other compounds), and acetic acid has been selected as a model compound. The experimental work has been conducted in a fluidized-bed reactor. Noncatalytic steam reforming of acetic acid has been performed from 450 °C to 700 °C. For catalytic experiments, coprecipitated Ni-Al catalysts, some promoted with lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(89 citation statements)
references
References 36 publications
3
81
2
3
Order By: Relevance
“…The deactivation of the catalyst decreases the CO 2 and H 2 yields and increases the CO and CH 4 yields. Galdámez et al [25] and Ramos et al [26] explained the role of the catalyst in these reactions in the steam reforming of model compounds of bio-oil.…”
Section: Influence Of Catalyst Compositionmentioning
confidence: 99%
“…The deactivation of the catalyst decreases the CO 2 and H 2 yields and increases the CO and CH 4 yields. Galdámez et al [25] and Ramos et al [26] explained the role of the catalyst in these reactions in the steam reforming of model compounds of bio-oil.…”
Section: Influence Of Catalyst Compositionmentioning
confidence: 99%
“…One of the most promising ways for employing biomass to produce hydrogen is SR of bio-oil obtained by fast-pyrolysis of biomass resources [5][6][7]. Garcia L. [8] and Galdamez J.R. [9] conducted the SR of bio-oil in fixed-bed micro-reactor and fluidized-bed reactor under different conditions respectively, (CP), wet impregnation (WI) and ion exchange (IE). The results of characterizations demonstrated that differences in crystal structure and MSI caused by different preparations have altered the reducibility of the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…And till now, many research institutes have done a lot of work on steam reforming of bio-oil [13][14][15][16][17][18]. Most studies are based on the fixed bed reactor and some are conducted in fluidized beds [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%